Self-initiated expatriation: changing the ontological and methodological box. Issue 3 (12th September 2016) - McKenna, Steve; Richardson, Julia
Abstract : Purpose: The purpose of this paper is to offer an ontological and methodological alternative to the functionalist paradigm which currently dominates study of the self-initiated expatriate (SIE). It argues conceptually, and with a practical example, that actor-network theory (ANT) offers an alternative way forward. While the functionalist study of SIE seeks to generate knowledge of value to organizations, ANT seeks to produce practical knowledge from the viewpoint of the SIE(s). Design/methodology/approach: The paper critiques the dominant functionalist approach to the study of SIE through ANT. A case history of a geographically mobile professional is offered to support the use of ANT as an ontological and methodological alternative in this field. Findings: By following the actors through their own stories of mobility the authors argue that it is possible to offer alternative ways of investigating and understanding mobility. In particular, actors enact mobility in unique ways as they move and are, therefore, not easily categorized and in singular classifications, such as the "SIE." Originality/value: The study of SIE is an important emerging field of expatriate research. It is currently dominated by the functionalist paradigm. The paper offers an alternative ontological and methodological approach to the study of this field through the use of ANT. In this sense the authors challenge the developing dominant discourse of functionalism currently driving research on this topic.